Skin metabolism phase I and phase II enzymes in native and reconstructed human skin: a short review. Issue 9 (September 2019) - Kazem, Siamaque; Linssen, Emma Charlotte; Gibbs, Susan
Highlights: Understanding human skin models encourages their use in xenobiotic metabolism testing. Skin models indicate relevant expression and activity of phase II metabolizing enzymes. Skin shows properties of chemical detoxification and elimination in vitro and ex vivo . More physiologically relevant models (e.g., skin-on-a-chip) are expected in the near future. Abstract : Understanding skin metabolism is important when considering drug discovery and safety assessment. This review compares xenobiotic skin metabolism in ex vivo skin to reconstructed human skin and reconstructed human epidermis models, concentrating on phase I and phase II enzymes. Reports on phase I enzymes are more abundant than for phase II enzymes with mRNA and protein expression far more reported than enzyme activity. Almost all of the xenobiotic metabolizing enzymes detected in human skin are also present in liver. However, in general the relative levels are lower in skin than in liver and fewer enzymes are reported.